Coordination chemistry and biological activity of two tridentate ONS and NNS Schiff bases derived from S-benzyldithiocarbazate - Tofazzal, M.; Tarafder, H.; Ali, Manaf A.; Saravanan, N. (Kluwer Academic Publishers, 2000)
Two tridentate Schiff bases having ONS and NNS donor sequences were prepared by condensing S-benzyldithiocarbazate (NH2NHCSSCH2Ph) (SBDTC) with pyridine-2-carboxaldehyde and salicylaldehyde, respectively. Complexes of these ligands with NiII, ZnII, CrIII, CoII, CuII, and SnII were studied and characterized by elemental analyses and various physico-chemical techniques. NiII, CuII, ZnII and SnII complexes were four-coordinate while the CrIII, SrIII and CoIII complexes were six-coordinate. The ONS Schiff base was moderately active against leukemia, while its zinc, antimony and cobalt complexes were strongly active against leukemic cells with DC50 = 0.35-5.00.